Model Sinektik Untuk Meningkatkan Kemampuan Analisis Matematis Pada Siswa MTS Ushuluddin Singkawang - Ariska, Tia; Mariyam, Mariyam; Utami, Citra (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
AbstractThis study aims to determine the improvement of students' mathematical analysis skills, individual and classical learning completeness, and student learning interest in the tangent material of the VIII class MTs Usshuludin Singkawang by applying the Synectic learning model. This study uses a Quasi-Experimental design using the Nonequivalent Control Group form, the population in this study are all classes of VIII MTs Usshuludin Singkawang consisting of 5 classes totaling 149 people. The sample was taken using the Random Sampling Cluster technique, while the sample consisted of two classes, namely class VIII B (29 students) as an experimental class and class VIII D (30 students) as a control class. The data analysis technique used was the 1 sample t-test to calculate individual completeness, the proportion test to calculate classical completeness, the two independent sample t-tests to calculate differences in mathematical analysis ability improvement, and the one variable t / z test to calculate student interest in learning. The results showed: 1) There was mastery learning both individually and classically that got direct learning using synectic models, 2) There was a difference in the improvement of students 'mathematical analysis skills, the increase in the experimental class was higher than in the control class, 3) The students' interest in learning after being applied to learn using synectic learning models can reach more than 70% of the ideal value.Â Keywords: Synectic Learning Model, mathematical analysis ability, mastery learning, student interest in learning